NATURAL RADIONUCLIDE CONTENT AND RADIOLOGICAL HAZARD ASSOCIATED WITH USAGE OF QUARTZITE SAND SAMPLES FROM OVACIK–SILIFKE–MERSIN OPEN PIT AS BUILDING MATERIAL IN TURKEY - Turhan, Şeref; Aykamış, A.Ş.; Kılıç, A.M. (Radiation Protection Dosimetry, 2009)
Activity concentrations of 238U, 232Th, 226Ra and 40K in quartzite sand samples collected from the Ovacık–Silifke–Mersin open pit located in the East Mediterranean region of Turkey were determined by using a gamma-ray spectrometry technique. The mean activity concentrations of the 238U, 232Th, 226Ra and 40K in quartzite sand samples were found as 81.7+ 22.9 Bq kg21 , 6.3+ 2.8 Bq kg21 , 77.5+ 24.3 Bq kg21 and 140.0+ 124.1 Bq kg21 , respectively. The gamma index (Ig), the internal exposure index (Ia), the indoor absorbed dose rate (Din) and the corresponding annual effective dose (Hin) were evaluated for the public exposure to radiological hazard arising due to the use of quartzite sand samples as building material. The values of Ig, Ia, Din and Hin ranged from 0.20 to 0.75, with a mean of 0.34+ 0.11, 0.23 to 0.77 with a mean of 0.39+ 0.12, 58.27 to 201.51 nGy h21 with a mean of 93.33+ 27.63 nGy h21 and 0.29 to 0.99 mSv with a mean of 0.46+ 0.14 mSv, respectively.